Laḫmu, the Divine Gatekeeper and Warrior: On the Meaning of lḥm in Deut 32:24 and Judg 5:8 - Wang, Jinyan (Antiguo Oriente, 2025)
In this paper, it is argued that in Deut 32:24 and Judg 5:8, לחם (lḥm) can be interpreted as references to the Mesopotamian Laḫmu, a category of minor deities who served as gatekeepers for higher gods and who also served as divine warriors and protective spirits. It is argued that Deut 32:24 refers to Resheph and Qeteb as the “Laḫmus of Yahweh” (“my Laḫmus”) in reference to their roles as Yahweh’s attendants and agents of punishment, while Judg 5:8 refers to Deborah as the “Laḫmu of the gates,” emphasizing her role as the guardian and warrior of her community in difficult and chaotic times.